Feasibility of alibangbang (Bauhinia Malabarica) as a potential source of natural dye - Colarina, Krizzele Edriel Tisalona
ABSTRACT This thesis aimed to determine a potential source of natural dye from a plant growing abundantly in the Philippines: the Alibangbang or Malabar orchid. The bark of the Alibangbang tree was utilized as the source of dye due to its tannin content, from which a reddish brown substance was extracted during highly controlled laboratory methods. After extraction, the substance was viewed with a spectrophotometer on cotton and cotton-polyester blends for Color Reflectance Value, and then put through wash tests for Colorfastness to Laundering. The colors that the extract provided were a variety of shades and tints of brown. On a scale of 1 to 5, being the highest, the samples rated at 1 to 1.5 for fastness to laundering, thus failing the fastness to laundering test but passing the staining test with ratings ranging from 4 to 4.5. The samples with the strongest color are those subjected to 5% mordant concentration and 200% dye concentration. The increased awareness of ecological degradation has led to higher demand for natural products, and this is evident in chemical-free products preferred by consumers. With this, the Philippine Textile Research Institute has started research on natural dyes and dyeing techniques which can eventually lessen the toxic discharges of dyeing. This study can also aid PTRI's goal to help small and medium scale businesses by providing an organic source of dye and lessening the toxic chemicals needed.